Willingness to pay for QALY: perspectives and contexts in Japan. (3rd October 2019) - Igarashi, Ataru; Goto, Rei; Yoneyama-Hirozane, Mariko
Abstract: Objectives: Theoretically, willingness-to-pay (WTP) for quality-adjusted life years (QALY) can vary depending on social and personal preferences and on ex-ante and ex-post settings. However, empirical investigations into the theoretical differences are lacking. In Japan, setting the threshold has been controversial since a pilot project to implement health technology assessments (HTA) launched in 2016. The study aim is to estimate WTP values for one additional QALY from different perspectives, health statuses, and contexts to confirm the difficulty in setting a uniform price threshold using WTP. Methods: More than 1, 000 respondents representing a cross-section of the Japanese population answered each of nine questionnaire decks in an online panel. WTP values were estimated on three different perspectives (personal, social, and socially inclusive) and on two contexts (ex-ante and ex-post). This study primarily used the non-parametric spike model based on double-bounded dichotomous choice (DBDC) settings to obtain the conditional WTP values. Results: WTP per QALY was higher in the severe health status than in the moderate health status from all perspectives. Respondents from the socially inclusive perspective estimated the highest WTP value for a new drug. Respondents were also asked about life-threatening diseases in ex-post and ex-ante. The WTP value in ex-ante was higher than in ex-post, and demographic factors affecting the WTP were different in both situations. The various WTP values were obtained from these surveys. Limitations: The analysis was based on data collected from an internet panel, which could be biased. There is also a risk that respondents answered the questionnaire differently if asked in everyday situations. Conclusion: Use of a uniform price threshold may not be appropriate in policy settings, because it may not reflect diverse preferences based on different situations, such as disease type and severity. Setting a price threshold as Japan institutes an HTA system requires further research.